Analysis of information synergy between e-Waybill solutions and intelligent transport system services. (1st January 2013) - Bakhtyar, Shoaib; Holmgren, Johan; Persson, Jan A.
We present a study on information synergy between an electronic waybill (e-Waybill) and intelligent transportation system (ITS) services. A waybill is an important transport document, and it contains essential information about a consignment. We consider five e-Waybill solutions, which differ in where the e-Waybill information is stored, read, and written. We analyse 20 ITS services, and for each of them, the required input entities that can be provided by an e-Waybill are identified, and the synergy with each of the e-Waybill solutions is determined based on the location of the e-Waybill information. The analysis shows that e-Waybill solutions with storage at the freight-level enable the highest information synergy with ITS services. Our result may support the implementation of practical e-Waybill systems that provide high synergy with ITS services, which may lead to higher utilisation of ITS services and more sustainable transport, e.g., in terms of reduced congestion and emissions.